Computational Biomechanics for Medicine From Algorithms to Models and Applications - Wittek, Adam.; Joldes, Grand; Nielsen, Poul M.F.; Doyle, Barry J.; Miller, Karol; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This volume comprises the latest developments in both fundamental science and patient-specific applications, discussing topics such as: cellular mechanics; injury biomechanics; biomechanics of heart and vascular system; medical image analysis; and both patient-specific fluid dynamics and solid mechanics simulations. With contributions from researchers world-wide, the Computational Biomechanics for Medicine series of titles provides an opportunity for specialists in computational biomechanics to present their latest methodologies and advancements.
Chapter1. The Effects of Geometric Variation from OCT-Derived 3D Reconstructions on Wall Shear Stress in a Patient-Specific Coronary Artery -- Chapter2. Constitutive Modelling of Lamb Aorta -- Chapter 3. Quantifying Cytoskeletal Morphology in Endothelial Cells to Enable Mechanical Analysis -- Chapter 4. Computational Approaches for the Modelling of Atherosclerotic Plaque Progression -- Chapter5. Reduced Order Model of a Human Left and Right Ventricle Based on POD Method -- Chapter6. Estimation of the Permeability Tensor of the Microvasculature of the Liver through Fabric Tensors -- Chapter7. Motion Estimation with Finite-Element Biomechanical Models and Tracking Constraints from Tagged MRI -- Chapter8. Subpixel Measurement of Living Skin Deformation Using Intrinsic Features -- Chapter9. Three-Dimensional Glenohumeral Joint Kinematic Analyses From Asynchronous Biplane Fluoroscopy Using an Interpolation Technique -- Chapter10. An Evaluation of Adaptive Biomechanical Non-Rigid Registration forBrain Glioma Resection using Image-Guided Neurosurgery -- Chapter11. Registration of Prone and Supine Breast MRI for Breast Cancer Treatment Planning -- Chapter12. Evaluation of Strains on Levator Ani Muscle: Damage Induced During Delivery for a Prediction of Patient Risks -- Chapter.13. Abusive Head Trauma - Developing a computational Adult Head Model to Predict Brain Deformations Under Mild Accelerations -- Chapter14. Computation of Brain Deformations Due to Violent Impact: Quantitative Analysis of the Importance of the Choice of Boundary Conditions and Brain Tissue Constitutive Model. .
Keywords: Biomedical engineering; Mathematics -- Data processing; Mechanics, Applied; Radiology; Medical physics; Control engineering; Robotics; Automation; Biomedical Engineering and Bioengineering; Computational Science and Engineering; Engineering Mechanics; Radiology; Medical Physics; Control, Robotics, Automation